Perancangan Dokumen ISO 9001:2015 Sebagai Persiapan Sertifikasi di CV XYZ - Enrico Alexander; Jani Rahardjo (Jurnal Titra, 2023)
CV XYZ is a company engaged in construction planning and consultancyservices. CV XYZ requires ISO 9001:2015 certification in order to apply for the extensionof their Business License. The challenge faced is that the company does not yet have thecomplete set of documents required for ISO 9001:2015 certification application. Thedocumentation completeness was designed to enable CV XYZ to apply for ISO 9001:2015certification. Initially, an initial gap analysis was conducted to determine the existing document completeness before the document design began. The initial gap analysis resultsshowed a total document completeness percentage of 4.55%, with only one document beingcomplete. Document design was then carried out for each clause of ISO 9001:2015, tailored to the company's situation and condition. After completing the document design and conducting validation, the final gap analysis results showed a total document completeness percentage of 100%. There was a 95.45% increase in the total document completeness percentage compared to the initial gap analysis, with 21 documents being designed.